Robotic Process Automation in Accounting - Domenico, Daniela Di; Zanetti, Micheli; Mazzioni, Sady; Três, Naline; Nodari, Douglas (Journal of Cultural Analysis and Social Change, 2026)
This study aims to investigate the adoption of Robotic Process Automation (RPA) in the accounting field in the region of Chapecó, Santa Catarina, Brazil, analyzing its influence on processes, professionals’ perceptions, and the challenges faced. The research adopted a descriptive and quantitative approach through the application of structured questionnaires conducted electronically with a sample of accounting professionals from the Chapecó region in the state of Santa Catarina. The results reveal a growing use of automation tools, especially for routine tasks, contributing to cost reduction, increased efficiency, precision, and agility in accounting routines, in addition to improving the quality of the work performed. The conclusions reinforce the importance of a proactive stance regarding professional training and the adoption of technological innovations to consolidate digital transformation in the accounting sector, supporting competitiveness and the strategic role of accounting professionals. The study contributes to the understanding of the current scenario of automation in regional accounting and provides insights into future technological implementation initiatives in the field.